2016
DOI: 10.1016/j.mambio.2015.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Morphological disparity, conservatism, and integration in the canine lower cervical spine: Insights into mammalian neck function and regionalization

Abstract: The neck skeleton is constituted as a highly mobile, multi-element and multi-joint kinematic chain. This construction leads to a kinematic redundancy on several levels. The problem of coordinating a large number of joints and muscles is solved by reducing the degrees of freedom to only few preferred motor axes. This is achieved by the regionalization of the cervical spine into three functional compartments. However, the neck skeleton traditionally is only partitioned into two units basing on the derived morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 63 publications
7
43
0
Order By: Relevance
“…Three recent studies have shown that phenotypic integration patterns of the cervical vertebral column are both highly conserved and highly predictable in felids and canids (Arnold et al. ; Randau and Goswami , b), generally in line with the predicted genetic and functional modules (Kessel et al. ; Kessel and Gruss ; Buchholtz et al.…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…Three recent studies have shown that phenotypic integration patterns of the cervical vertebral column are both highly conserved and highly predictable in felids and canids (Arnold et al. ; Randau and Goswami , b), generally in line with the predicted genetic and functional modules (Kessel et al. ; Kessel and Gruss ; Buchholtz et al.…”
mentioning
confidence: 86%
“…Arnold et al. () did not include C1–C2, but found that C6 and C7 appear to form a different module than C3 through C5. They also found that the vertebral spine and vertebral body are highly integrated, so that cervical vertebrae appear to be formed of a single module, rather than multiple modules (Arnold et al.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have revealed processes in the prenatal development constraining meristic variability in the neck (Galis 1999; Galis and Metz 2003;Galis et al 2006;Galis and Metz 2007;Buchholtz 2012;Buchholtz et al 2012;Hirasawa and Kuratani 2013;Buchholtz 2014;Hirasawa et al 2016). The pattern of vertebral size modification is hence of particular importance, as the general shape of the individual vertebrae (C1-C7) is quite conserved across mammalian lineages and their body size range (Johnson and O'Higgins 1996;Johnson et al 1999;Buchholtz and Stepien 2009;Buchholtz et al 2012;Buchholtz et al 2014;Arnold et al 2016). In some mammalian clades, however, natural selection favored the increase or the decrease in neck length, such as in giraffes and whales, respectively.…”
mentioning
confidence: 99%
“…Randau and Goswami () examined intravertebral integration in the presacral vertebrae of members of the Felidae, using geometric morphometric methods to quantify shape. Arnold et al, Forterre, Lang, and Fischer () used similar techniques to examine intravertebral integration in the cervical vertebrae of canids.…”
Section: Introductionmentioning
confidence: 99%